Projected effects of climate change and urban expansion on species-level biodiversity of plants in main city clusters of Northern China - Ma, Tianxiao; Liang, Yu; Li, Zhouyuan; Liu, Bo; Wu, Mia M.; Lau, Matthew K.; Feng, Yue (Frontiers in Ecology and Evolution, 2023)
Northern China is considered a global hotspot of biodiversity loss due to dramatic climate and land use change characterized by rapid urban expansion. However, little is known that the impacts of these two drivers in shaping the future availability of habitat for plants in urban areas of Northern China, especially at a high spatial resolution. Here, we modelled the habitat suitability of 2,587 plant species from the flora of Northern China and estimated how future climate and urban expansion may affect species-level plant biodiversity across three shared socioeconomic pathway (SSP) scenarios for the year 2050 in main city clusters. The results suggested that climate and urban expansion combined could cause a decline of up to 6.5% in plant biodiversity of Northern China, while urban expansion alone may cause 4.7-6.2% and climate change cause 0.0-0.3% by 2050. The contribution of urban expansion was higher in urban areas, while the contribution of climate change was higher in natural areas. Species may lose an average of 8.2-10.0% of their original environmentally suitable area. Our results verified that the process of urban expansion would necessarily result in large-scale biodiversity loss. The plant biodiversity loss in city clusters of Northern China was mainly determined by urban expansion rather than climatic change. The impact of climate change should not be ignored, since climate change will likely cause a higher reduction of area for some species. Based on these findings, we proposed that plant biodiversity loss in Northern China will accelerate in the future unless both urban expansion change and climate change are minimized.